2021
DOI: 10.1111/jnc.15520
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial protein REG3A and signaling networks are predictive of stroke outcomes

Abstract: Regenerating Family Member 3 Alpha (REG3A) is a multifunctional protein with antimicrobial activity, and primarily secreted by the intestine and pancreas. Studies have shown an increased expression of REG3A in systemic inflammatory responses to acute injury and infection, but studies investigating REG3A during the pathogenesis of ischemic stroke are limited. The aims of this study were to examine the associations between arterial expression of REG3A and other arterial inflammatory proteins implicated in stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…191,194,195 In a study of 40 ischemic stroke patients, Reg3 was positively correlated with IL-6/17C and a higher NIHSS score, suggesting it is upregulated in response to ischemic stroke. 191 Another gut hormone, trefoil factor-3 (TFF-3), is secreted from goblet cells and supports mucosal integrity and healing postinjury. 192 In an animal model of stroke, TFF-3-deficient mice exhibited significantly higher levels of cell death and cerebral infarcts; intravenous administration of recombinant TFF-3 reversed cerebral injury and improved motor function.…”
Section: Postulated Mechanisms By Which the Gut-brain Axis Becomes Dy...mentioning
confidence: 99%
See 1 more Smart Citation
“…191,194,195 In a study of 40 ischemic stroke patients, Reg3 was positively correlated with IL-6/17C and a higher NIHSS score, suggesting it is upregulated in response to ischemic stroke. 191 Another gut hormone, trefoil factor-3 (TFF-3), is secreted from goblet cells and supports mucosal integrity and healing postinjury. 192 In an animal model of stroke, TFF-3-deficient mice exhibited significantly higher levels of cell death and cerebral infarcts; intravenous administration of recombinant TFF-3 reversed cerebral injury and improved motor function.…”
Section: Postulated Mechanisms By Which the Gut-brain Axis Becomes Dy...mentioning
confidence: 99%
“…186 The GI tract contains the largest endocrine "organ" in the body, the enteric endocrine cells, which can release biologically active "gut-derived" hormones (e.g., cholecystokinin, chromogranin, gastrin, glucagon-like peptide-1, norepinephrine, secretin, serotonin, and somatostatin) with complex immune and/or protective actions that may play a role in ischemic stroke. 130,[186][187][188][189][190][191][192] An imbalance of gut hormones can perpetuate GI dysbiosis; for example, a higher concentration of norepinephrine can lead to opportunistic pathogen proliferation, 193 which has been demonstrated in an experimental stroke model. 145 Further, gut-derived hormones likely play a role in responding to the proinflammatory response poststroke.…”
Section: Postulated Mechanisms By Which the Gut-brain Axis Becomes Dy...mentioning
confidence: 99%
“…20,21 REG3A is a multifunctional protein with antimicrobial activity, and primarily secreted by the intestine and pancreas. 22 Studies have shown an increased expression of REG3A in systemic inflammatory responses to acute injury and infection. 23,24 More importantly, enteric delivery of REG3A was revealed to alter the intestinal microbiota and controls inflammation in UC model mice.…”
Section: Introductionmentioning
confidence: 99%
“…REG proteins are associated with the pathogenesis in the gastrointestinal (GI) tract 20,21 . REG3A is a multifunctional protein with antimicrobial activity, and primarily secreted by the intestine and pancreas 22 . Studies have shown an increased expression of REG3A in systemic inflammatory responses to acute injury and infection 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously published studies that used this protocol have provided novel data relating proteomic characteristics with clinical outcomes. These studies have shown that there are significantly lower intracranial expressions of proteins involved in th2 and neutrophil proliferation [i.e., C-C motif chemokine 19 (CCL19), 20 (CCL20), and 23 (CCL23)] during stroke (30) and that the expression of various cytokines, chemokines, and inflammatory proteins taken at the time of thrombectomy may predict stroke severity (30)(31)(32)(33). More so, alterations in peri-infarct blood gases and electrolytes were found to exist during stroke, and some of these are sex-specific (34,35).…”
Section: Introductionmentioning
confidence: 99%